2016
DOI: 10.1016/j.cbpa.2016.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity pulsed ultrasound induces apoptosis in osteoclasts: Fish scales are a suitable model for the analysis of bone metabolism by ultrasound

Abstract: Using fish scales in which osteoclasts and osteoblasts coexist on the calcified bone matrix, we examined the effects of low-intensity pulsed ultrasound (LIPUS) on both osteoclasts and osteoblasts. At 3 hours of incubation after LIPUS treatment, osteoclastic markers such as tartrate-resistant acid phosphatase (TRAP) and cathepsin K mRNA expressions decreased significantly while mRNA expressions of osteoblastic markers, osteocalcin, distal-less homeobox 5, runt-related transcription factor 2a, and runt-related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
0
21
1
Order By: Relevance
“…used LIPUS on zebrafish scales (containing both osteoblasts and osteoclasts) for 20 min. Results showed that LIPUS can cause osteoclast apoptosis in their model34. The current study is different from Suzuki’s study.…”
Section: Discussioncontrasting
confidence: 92%
“…used LIPUS on zebrafish scales (containing both osteoblasts and osteoclasts) for 20 min. Results showed that LIPUS can cause osteoclast apoptosis in their model34. The current study is different from Suzuki’s study.…”
Section: Discussioncontrasting
confidence: 92%
“…Focused low-intensity pulsed ultrasound (FLIPUS) affected ECM production in KOA rabbits by decreasing chondrocyte apoptosis [46]. Conversely, LIPUS treatment promoted apoptosis and decreased the viability of endothelial cells, osteoclasts, and preadipocytes in human [47][48][49]. The opposite results may attribute to different parameters of LIPUS and different cells.…”
Section: Discussionmentioning
confidence: 99%
“…Using GeneChip analysis of zebrafish scales treated with LIPUS, we found that cell death-related genes were upregulated (21). Furthermore, the multinuclei of TRAP-stained osteoclasts in the scales were labeled with TUNEL for DNA breaks (21). Our previous report (21) indicates that LIPUS directly functions in osteoclasts and promotes apoptosis in osteoclasts shortly after exposure.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Therefore, the data of mammalian hard tissue support our present results. Using GeneChip analysis of zebrafish scales treated with LIPUS, we found that cell death-related genes were upregulated (21). Furthermore, the multinuclei of TRAP-stained osteoclasts in the scales were labeled with TUNEL for DNA breaks (21).…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation